Perawatan Luka Diabetikum pada Klien dengan Gangren - Ruswati Ruswati; Titin Supriyatin; Gilang Pranajasakti (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Diabetes Mellitus is a metabolic disease caused by problems in the body in producing insulin, insulin produced is lacking or nonexistent, or it can be due to the insulin receptor not functioning so that cells cannot receive glucose for metabolism (Black, M. J. & Hawks, 2014; Pranata, S & Khasanah, 2017). Diabetic wounds are caused by infection as a result of high blood glucose, thereby increasing bacterial proliferation, and added to the deficiency of the immune system which causes the wound inflammation period to last a long time. In addition, inappropriate treatment of diabetic wounds (ulcers) can worsen the condition of the wound (Ekaputra, 2013). Therefore, proper and optimal wound care is needed. The wound care method that is currently developing is moist wound healing, which is more effective than conventional methods because it is easy to install, can adjust to the shape of the wound, easy to remove, comfortable to wear, does not need to change dressings frequently, absorbs drainage, presses and immobilizes wounds, prevents new wounds from mechanical injury, prevents infection, improves hemostasis by pressing the dressing. Wound care procedures through Debridement and dressing. Wound debridement can accelerate healing by removing necrotic tissue, particulates, or foreign material, and reducing the bacterial load. The conventional method is to use a scalpel and cut away all unwanted tissue including callus and eschar. Saline-moistened (wet-to-dry) gauze dressings; moisture-retaining dressings (hydrogels, hydrocolloids, hydrofibers, transparent films and alginates) that provide physical and autolytic debridement respectively; and antiseptic dressings (silver dressings, cadexomer). Newer advanced dressings are being studied, such as Vulnamin gel made from amino acids and hyaluronic acid used in conjunction with elastic compression have shown positive results.